Hubungan Antara Posisi Anak Dalam Keluarga DenganKemandirian Di Paud Se-Desa Tohudan, Colomadu, Karanganyar Tahun Pelajaran 2015/1016 - ANDARINI, Ika Ayu (2016)
The purpose of the research 1) was to determine the difference of autonomy in terms of the position of the child on PAUD in the village Tohudan, Colomadu, Karanganyar. 2) was to autonomy order in terms of the position of the child on PAUD in the village Tohudan, Colomadu, Karangyar. This research is a comparative descriptive. The population in this research as many as 69 childrens and sampel as many as 56. The technique of sampling using disproportionate stratified random sampling. Collection techniques such as document and questionnaires. Analysis of the result using One Way Anova. The result show F_(count )=0,602 and F_table=2,78 and p=0,617 (>0,05), So that Ho accepted and Ha refused means there is don't difference of autonomy in terms of the position of the child. The order of autonomy is eldest, youngest, middle and the last is single.